Lucas on the relationship between theory and ideology - Michel De Vroey (Kiel Institute for the World Economy (IfW), 2010)
This paper concerns a neglected aspect of Lucas's work: his methodological writings, published and unpublished. Particular attention is paid to his views on the relationship between theory and ideology. I start by setting out Lucas's non-standard conception of theory: to him, a theory and a model are the same thing. I also explore the different facets and implications of this conception. In the next two sections, I debate whether Lucas adheres to two methodological principles that I dub the 'non-interference' precept (the proposition that ideological viewpoints should not influence theory), and the 'non-exploitation' precept (that the models' conclusions should not be transposed into policy recommendations, in so far as these conclusions are built into the models' premises). The last part of the paper contains my assessment of Lucas's ideas. First, I bring out the extent to which Lucas departs from the view held by most specialized methodologists. Second, I wonder whether the new classical revolution resulted from a political agenda. Third and finally, I claim that the tensions characterizing Lucas's conception of theory follow from his having one foot in the neo-Walrasian and the other in the Marshallian-Friedmanian universe.
Keywords: B22; B30; B31; B41; 330; Lucas; new classical macroeconomics; methodology; Neue klassische Makroökonomik; Wissenschaftliche Methode; Dogmengeschichte